2003
DOI: 10.1074/jbc.m208670200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Superoxide Dismutase Isoform Expression on Hydroperoxide-induced Apoptosis in PC-12 Cells

Abstract: The current study examines the contribution of mitochondria-derived reactive oxygen species (ROS) in tertbutyl-hydroperoxide (TBH)-induced apoptotic signaling using clones of undifferentiated pheochromocytoma (PC-12) cells that stably overexpress the human mitochondrial or cytoplasmic forms of superoxide dismutase (SOD) (viz. Mn-SOD or CuZn-SOD, respectively). Exposure of wild type cells to TBH caused an early generation of ROS (30 min) that resulted in cell apoptosis at 24 h. These responses were attenuated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 33 publications
4
79
0
3
Order By: Relevance
“…6). These results, while in agreement with the role played by this enzyme in modulating the sensitivity of cancer cells to external or cytosolic-derived superoxide [19], may also be in line with the ineffectiveness of Cu,Zn SOD to counteract mitochondrial-mediated ROS production [20].…”
Section: Discussionsupporting
confidence: 85%
“…6). These results, while in agreement with the role played by this enzyme in modulating the sensitivity of cancer cells to external or cytosolic-derived superoxide [19], may also be in line with the ineffectiveness of Cu,Zn SOD to counteract mitochondrial-mediated ROS production [20].…”
Section: Discussionsupporting
confidence: 85%
“…9, 24 We further found that an induction of GSH/GSSG imbalance per se directly initiated apoptosis in these cells without ROS involvement. 10 The current results show that TBH-induced apoptosis in dPC12 cells is similarly mediated by cellular GSH/GSSG redox, and that cellular redox play a causal role in apoptosis initiation.…”
Section: Resultsmentioning
confidence: 63%
“…Figure 8c shows that 20% apoptosis of dPC12 cells was observed at 300 mM TBH that was comparable to that after treatment of nPC12 cells with 100 mM TBH. 24 Accordingly, a greater magnitude of early decreases in cellular GSH with increases in GSSG and attenuated GSH-to-GSSG ratios were achieved with treatment of cells at 300 mM TBH (Figures 9a-c).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This protective ability of SOD2 in DRG in vitro is consistent with other studies using SOD2 overexpression. SOD2 overexpression eliminates pro-oxidantinduced mitochondrial ROS in PC-12 cells and decreases cell injury (Pias et al, 2003). Similarly, in retinal pigment epithelial cells, the gene dosage of SOD2 directly relates to the degree of mitochondrial injury and apoptosis induced by H 2 O 2 (Kasahara et al, 2005).…”
Section: Discussionmentioning
confidence: 97%